Lionel Meunier and Vox Luminis perform Handel At the Royal Chapel of the Palace of Versailles - Handel, George Frideric; Handel, George Frideric; Handel, George Frideric; Handel, George Frideric (Les Films Figures Libres - Mezzo - Opéra Royal - Château de Versailles Spectacles, 2018)
The lively colors, infinite textures and striking shapes that adorn the interior of the Royal Chapel of Versailles provide a stunning backdrop for the exquisite choral music of George Frideric Handel, the famed Baroque composer who was born in Germany, trained in Italy, and nationalized as English. In his life and work, Handel embodied much of what the Baroque represented: a meeting point between the arts and styles of different eras and diverse nations, deployed with technical mastery. The Gramophone Award-winning ensemble Vox Luminis, led by Lionel Meunier, give brilliant perspective to two Italian-inspired works by the young Handel, 1707's Nisi Dominus and Dixit Dominus, juxtaposed with a more mature work, the Ode for St. Cecilia's Day (1739), written in London and inspired by the Pythagorean idea of music as a central force in the Earth's creation
Keywords: concert; Webcast; Internet videos; Vidéos sur Internet